2022
DOI: 10.3324/haematol.2022.280755
|View full text |Cite
|
Sign up to set email alerts
|

Serum vascular endothelial growth factor is associated with cardiovascular involvement and response to therapy in Erdheim-Chester disease

Abstract: Erdheim-Chester disease (ECD) is a rare histiocytosis, considered to be an inflammatory myeloid neoplasm. Tropism for specific involvements of the disease remains unexplained. Vascular endothelial growth factor-A (VEGF) is implicated in cancer pathophysiology and mutations of the RAS oncogene have been shown to induce the upregulation of VEGF gene expression. We therefore hypothesized that VEGF might play a particular role in ECD pathophysiology. We conducted a retrospective monocenter study to assess serum VE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…High levels are significantly associated with cardiovascular involvement and improvement in VEGF mirrors cardiovascular response to treatment and survival. 7 VEGF may serve as a method of detection and monitoring of cardiovascular manifestations in ECD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High levels are significantly associated with cardiovascular involvement and improvement in VEGF mirrors cardiovascular response to treatment and survival. 7 VEGF may serve as a method of detection and monitoring of cardiovascular manifestations in ECD.…”
Section: Discussionmentioning
confidence: 99%
“…5 Mutations in RAS genes, specifically KRAS and NRAS, are known to cause ECD and are associated with upregulation of vascular endothelial growth factor (VEGF) expression. 7 Roeser et al found that high serum VEGF levels (> 500 pg/mL) were associated with cardiovascular involvement. 8 They noted 68.8% of their patients with high VEGF had vascular involvement ('coated' aorta, mesenteric arteries, renal arteries) compared to 48.6% with low VEGF (p = 0.001).…”
Section: Epidemiologymentioning
confidence: 99%